Exploring the impact of physiotherapy on health outcomes in older adults with chronic diseases: a cross-sectional analysis - Reddy, Ravi Shankar; Alahmari, Khalid A.; Alshahrani, Mastour Saeed; Alkhamis, Batool Abdulelah; Tedla, Jaya Shanker; ALMohiza, Mohammad A.; Elrefaey, Basant Hamdy; Koura, Ghada M.; Gular, Kumar; Alnakhli, Hani Hassan; Mukherjee, Debjani; Rao, Vikram Sreenivasa; et al. (Frontiers in Public Health, 2024)
Objective: This study evaluates the impact of physiotherapy interventions on health outcomes and explores the correlation between physiotherapy session characteristics and improvements in health among older individuals.Methods: In a cross-sectional design, 384 older adults with chronic conditions such as arthritis, osteoporosis, Chronic Obstructive Pulmonary Disease (COPD), diabetes, and hypertension were recruited.Results: The proportion of arthritis (39.1%) and hypertension (45.8%) was notably high. Participants receiving physiotherapy showed significant improvements in pain levels (mean reduction from 5.09 to 2.95), mobility scores (improvement from 3.0 to 3.96), and functional independence. A positive correlation was identified between the frequency of physiotherapy sessions and pain reduction (r = 0.26, p = 0.035), and a stronger correlation between session duration and both pain reduction (r = 0.38, p = 0.002) and mobility improvement (r = 0.43, p = 0.001). High satisfaction rates with physiotherapy were reported, and age was found to be a significant negative predictor of health outcomes (Coef. = -0.3402, p = 0.0009).Conclusions: Physiotherapy interventions significantly improve health outcomes in older adults with chronic diseases.